2010
DOI: 10.1017/s1743921311011124
|View full text |Cite
|
Sign up to set email alerts
|

The multiplicity of massive stars

Abstract: Abstract. Binaries are excellent astrophysical laboratories that provide us with direct measurements of fundamental stellar parameters. Compared to single isolated stars, multiplicity induces new processes, offering the opportunity to confront our understanding of a broad range of physics under the extreme conditions found in, and close to, astrophysical objects.In this contribution, we will discuss the parameter space occupied by massive binaries, and the observational means to investigate it. We will review … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 37 publications
12
67
1
Order By: Relevance
“…Mason et al (1998) derived a binary fraction of ∼70% in massive field stars, although the exact numbers depend on the stellar spectral type considered (Raghavan et al 2010). In a clustered context, Sana & Evans (2011) and Sana et al ( , 2012a found a binary fraction of around 50% in young open clusters, including in the 30 Doradus region, which ties in very well with the ∼55% binary fraction quoted by Kobulnicky et al (2014) for the Cygnus OB2 association. Kouwenhoven et al (2005) studied the Scorpius OB2 association in detail and provided similar binary fractions, notably separated as a function of stellar spectral type.…”
Section: Introductionsupporting
confidence: 58%
“…Mason et al (1998) derived a binary fraction of ∼70% in massive field stars, although the exact numbers depend on the stellar spectral type considered (Raghavan et al 2010). In a clustered context, Sana & Evans (2011) and Sana et al ( , 2012a found a binary fraction of around 50% in young open clusters, including in the 30 Doradus region, which ties in very well with the ∼55% binary fraction quoted by Kobulnicky et al (2014) for the Cygnus OB2 association. Kouwenhoven et al (2005) studied the Scorpius OB2 association in detail and provided similar binary fractions, notably separated as a function of stellar spectral type.…”
Section: Introductionsupporting
confidence: 58%
“…Many of the most massive stars exist in tight (orbital periods of a few days) binaries (Zinnecker & Yorke 2007). For a recent update on massive binary properties, see Sana & Evans (2011).…”
Section: Formation Of Clusters and High-mass Starsmentioning
confidence: 99%
“…The presence of a nearby companion can strip the envelope from a star before it reaches giant dimensions, effectively reducing the number of red supergiants by up to 40% (assuming the distribution functions of Sana & Evans 2010). In addition, the accreting star or merger resulting from binary interaction may under certain circumstances produce blue supergiants as suggested for the progenitor of SN1987A and the companion of SN1993J (Hillebrandt et al 1987;Walborn et al 1989;Maund et al 2004).…”
Section: Interacting Binariesmentioning
confidence: 99%
“…Data from nearby open clusters suggest about 4 out of 10 O stars have companions that are nearby enough to interact (Sana & Evans 2010). Even though the fraction of stars whose properties have been altered by binary interaction may not be that large, the consequences of such interactions for the stellar luminosity are potentially severe due to the steep dependence of the luminosity on mass.…”
Section: Interacting Binariesmentioning
confidence: 99%